Productive performance of Holstein and the crossbreding Kiwi Cross x Holstein cattle - Mogollón-García, Henry David [UNESP]; Nieto-Sierra, David Felipe; Castro-Rincón, Edwin (Universidad de Costa Rica, 2020)
Introduction. During decades, milk production in the department of Nariño has depended on the Holstein breed. For this reason, it is necessary to evaluate a model of milk production that allows to decrease production costs and in turn improves the compositional quality of the milk. Objective. This study aimed was to compare the monthly milk production, days in lactation (DIM), and milk production per third of lactation of the F1 crossing of the Kiwi Cross (KC) and Holstein (HO) breeds, under grazing conditions in the high tropics of the Nariño department, Colombia. Materials and methods. Monthly milk production in HO cows (n=30) and F1 (n=40) was measured by adjusting the DIM, milk production was also obtained by third of lactation, fat, protein, and total solids. Results. Maximum production was higher for HO cows compared to KC (25.8±0.53 vs. 23.2±0.53 l day-1) (p<0.05). Production per third of lactation was higher (p<0.05) in the first third compared to the second and third periods for both breeds study (HO: 13.6±0.56 vs.11.3±0.5723 and 9.9±0.47 l day-1, and KC: 12.8±0.4505 vs. 10.6±0.66 and 9.5±1.69 l day-1). Fat was higher (p<0.05) in Kiwi Cross F1 crosses than in Holstein, at weeks one, three, and five (4±0.07, 4±0.07, 4±0.07 vs. 3.6±0.12, 3.6±0.11, 3.7±0.09 %, respectively); likewise, protein in weeks one and four was higher in the KC group compared to HO (3.3±0.04 vs. 3.1±0.05 %; p<0.05). Total solids were 13.3±0.17 vs. 12.5±0.23 % (p<0.05) for F1 and HO cows, respectively at weeks two and five. Conclusion. F1 and Holstein (HO) milk production was similar; however, KC improved the performance in the compositional milk quality, increasing the percentages of fat, protein, and total solids.
Rendimiento productivo de Ganado Holstein y el cruzamiento Kiwi Cross x Holstein
Keywords: Animal performance; Dairy cattle; Lactation; Milk yield